Estratégias de aprendizagem para o ensino de equação de primeiro grau com aluno surdo - Ariotti, Elisa (My University, 2024)
This research aimed to develop a teaching proposal for the learning of first-degree equations by a deaf student through the use of manipulative materials and games in the planning, implementation, and evaluation of a didactic sequence. It was adapted to the reality of a deaf student in Elementary School, specifically in the 7th grade of the Municipal School of Special Elementary Education "Caminhos do Aprender" in the municipality of Bento Gonçalves/RS. The dissertation presents exploratory research on first-degree equations through manipulative materials, games, and targeted activities, intending to provide the student with access to and understanding of this content, while seeking to explore their abstract logical reasoning. The games used in the didactic sequence are original, created by the author herself; some being adapted from other works, to enhance its use in the research context. All activities and games were planned with the aim of developing abstract logical reasoning and understanding of first-degree equations. Based on Vygotsky and Montessori, the research discusses language acquisition through the subject's interaction with the environment and the manipulation of objects for the construction and generalization of concepts. The result of this research is a didactic sequence called "A TEACHING PROPOSAL FOR FIRST-DEGREE EQUATIONS FOR DEAF STUDENTS." This didactic sequence includes targeted activities for reviewing content, the use of manipulative materials, and games for understanding first-degree equations. The data analysis from the research was qualitative, evaluating the research diary, notes, photographic records, vídeos, the development of activities with printed and manipulable materials, games and the academic protagonist of the research, who demonstrated learning and involvement beyond the researcher's expectations. It can be concluded that the educational product generated from this research has become a didactic resource with great potential for learning and developing abstract logical reasoning, providing a more accessible, understandable, and engaging teaching and learning process for first-degree equations. [resumo fornecido pelo autor]
Esta pesquisa teve por objetivo desenvolver uma proposta de ensino para a aprendizagem de equação do primeiro grau por um aluno surdo através da utilização de materiais manipuláveis e jogos no planejamento, aplicação e avaliação de uma sequência didática. Ela foi adaptada à realidade de um aluno surdo do Ensino Fundamental, especificamente no 7º ano, da Escola Municipal de Ensino Fundamental Especial Caminhos do Aprender no município de Bento Gonçalves/RS. A dissertação expõe uma pesquisa com a finalidade exploratória de equação de primeiro grau por meio de material manipulável, jogos e atividades direcionadas, com o intuito de proporcionar ao estudante o acesso e entendimento desse conteúdo, procurando explorar o raciocínio lógico abstrato dele. Os jogos utilizados na sequência didática são originais, produzidos pela própria autora, sendo alguns adaptados de outros trabalhos, de modo a potencializar a sua utilização no contexto da pesquisa. Todas as atividades e jogos foram planejadas com o objetivo de desenvolver o raciocínio lógico abstrato e compreensão de equação de primeiro grau. Com base em Vygotsky e Montessori, discute-se desde a aquisição da linguagem através da interação do sujeito com o ambiente até a manipulação de objetos para a construção e generalização de conceitos, resultando como produto desta pesquisa uma sequência didática denominada UMA PROPOSTA DE ENSINO DE EQUAÇÃO DE PRIMEIRO GRAU PARA ALUNOS SURDOS. Essa sequência didática integra atividades direcionadas de retomada de conteúdo, uso de material manipulável e jogos para a compreensão de equação de primeiro grau. A análise dos dados obtidos com a pesquisa foi qualitativa, avaliando-se o diário de bordo, anotações, registros fotográficos, vídeos, desenvolvimento das atividades com materiais impressos e manipuláveis, dos jogos e do acadêmico protagonista da pesquisa, o qual revelou aprendizagens e envolvimento para além das expectativas da pesquisadora. Pode-se concluir que o produto educacional gerado a partir desta pesquisa, tornou-se um recurso didático com grande potencial para a aprendizagem e o desenvolvimento do raciocínio lógico abstrato, propiciando um processo de ensino e de aprendizagem de Equação do primeiro grau mais acessível, compreensível e atrativo. [resumo fornecido pelo autor]
Keywords: Equações - Estudo e ensino (Ensino fundamental); Matemática (Ensino fundamental) - Estudo e ensino; Surdos - Educação; Jogos no ensino de matemática; Educação especial; Equations - Study and teaching (Elementary education); Mathematics (Elementary education) - Study and teaching; Deaf - Education; Games in mathematics education; Special education